Beneficial Effects of Multiple Plantation Patterns in Agroforestry Systems - Hymavathi, H. N.; Kandya, A. K.; Patel, L. E. (Indian Forester, 2010)
A survey was conducted in 150 agricultural fields where agroforestry has been followed. Five main multiple plantation patterns of agroforestry systems were followed which includes 2 to 6 plant species. It made 30 different crop geometries (CGs). In each pattern, there were several types of CGs mainly categorized on the basis of number of plant species grown in the central part of the agricultural field (1, 2, 3 or 4 species). All these types were usually followed by the farmers as per the local need, market demand of their product and financial gain to the farmers. The C : B ratio of various multiple plantation patterns has proved this fact.